Wybrane zmiany w polskim prawie bilansowym i podatkowym w świetle rozwiązań unijnych - Żuraw, Paweł (Selected Changes in Polish Balance and Tax Law in the Light of Union Solutions, 2005)
This article makes the readers think over some changes being introduced to Polish balance and tax law. If the new regulations in balance law do not evoke such emotions as changes in tax law, they still recquire a different, "non-standard" approach to accounting. It is connected with the permanent additional training of the financial-accounting service, improving work methods, gaining new abilities. It is certainly an undisputed matter, because it is recquired by the conforming process to Union directive. The argumentation is justified by the fact, that the adapting processes are to serve the common aim, which is the standardization of regulations, making the functioning on the homogenous European market easier.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 67-75